Influence of agility training on body-size and object solidity perception in pet dogs - Dario Starić; Lea Arnauer; Sarah Marshall-Pescini; Friederike Range (PLoS ONE, 2026)
Several studies suggest that dogs are a suitable model to study body-awareness in a systematic and ecologically relevant manner. However, previous studies used a single door paradigm, which does not allow for the control of motivation and thus may yield false positive results. Moreover, it is unclear how life experience might influence body-awareness. In this study, we tested self body-size and -shape as well as object solidity perception in pet dogs and agility trained dogs in a two-choice paradigm. The subjects had to walk through one of the two openings in a fence to reach a reward. The openings were of different shape and/or size (Experiment 1) or covered by different materials (Experiment 2). Dogs could correctly assess their size, while the results are less conclusive for shape perception. They also showed some understanding of the solidity of materials. Agility dogs took less time to reach the reward in Experiment 1, but took more time in Experiment 2. They also showed better shape perception. These results show that life experience has an effect on body-awareness.